2019
DOI: 10.1101/cshperspect.a036863
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches on Cancer Immunotherapy

Abstract: Metastasis, which occurs when cancer cells disseminate from the primary tumor site to other parts of the body, is the primary cause of mortality in patients, and the recurrence of multiple metastatic tumors is an obstacle to eliminating cancer. Recent clinical studies demonstrated that patients who respond to immunotherapy have longer survival rates with lower metastatic relapse, suggesting that immunotherapy may be one of the solutions to overcome cancer metastasis. Indeed, various host immune cells not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 125 publications
0
14
0
Order By: Relevance
“…In recent years, cancer immunotherapy has not only been paid more attention by the growing number of researchers, but also has been widely used in clinical practice ( 47 , 48 ). Although a variety of immunotherapy methods are available to treat tumors, including immune checkpoint inhibitors, cytokine, adoptive cell transfer, dendritic cell vaccines and chimeric antigen receptor T cells, immunotherapy based on immune checkpoint inhibitors have become the focus of attention ( 49 , 50 ). At the same time, tumor ablation has received extensive attention as a promising minimally invasive technique for the treatment of various tumors ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cancer immunotherapy has not only been paid more attention by the growing number of researchers, but also has been widely used in clinical practice ( 47 , 48 ). Although a variety of immunotherapy methods are available to treat tumors, including immune checkpoint inhibitors, cytokine, adoptive cell transfer, dendritic cell vaccines and chimeric antigen receptor T cells, immunotherapy based on immune checkpoint inhibitors have become the focus of attention ( 49 , 50 ). At the same time, tumor ablation has received extensive attention as a promising minimally invasive technique for the treatment of various tumors ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy is an effective treatment for cancer, mainly for the clinical treatment of recurrent or metastatic tumors ( Igarashi and Sasada, 2020 ; Quaglino et al, 2020 ). Basic and clinical studies have shown that antitumor immunity plays a key role in the development and progression of cancer ( Cha et al, 2020 ). Patients with UCEC reflect resemble clinical features, but due to molecular heterogeneity, they have distinct clinical results ( Li et al, 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there have been active attempts to restore CTL activity by blocking PD-L1/PD-1 signaling. FDA approved-ICBs, such as nivolumab, pembrolizumab, and atezolizumab, target PD-1 or PD-L1 ( 14 ).…”
Section: The Effect Of Metformin On Anti-tumor Immunitymentioning
confidence: 99%
“…Since T-cells are the main effector of anti-tumor immunity, T-cell activity has been the final target for most FDA-approved cancer immunotherapies [e.g., ICB (Ipilimumab, Nivolumab, Pembrolizumab, and Atezolizumab), dendritic-cell vaccine (Sipuleucel-T), and ACT (Axicabtageneciloleucel, and Tisagenlecleucel)] ( 14 ). However, since TIL activity is effectively inhibited by pro-tumoral TME, the efficacy of current immunotherapies is limited in most solid tumors.…”
Section: Introductionmentioning
confidence: 99%